Progress of Research on Advanced Non-Small Cell Lung Cancer with HER-2 Mutation - Liang ZHANG; Changliang YANG; Peidong LI; Ying CHENG (Zhongliu Fangzhi Yanjiu)
Anti-tumor drug research and development in non-small cell lung cancer (NSCLC) is rapidly developing, and the clinical application of high-throughput sequencing technology is also becoming widespread. Accordingly, researchers are focusing on human epidermal growth factor receptor-2 (HER-2) gene as a rare target of NSCLC, and a series of exploratory studies has been performed. Traditional chemotherapy and immunotherapy are unsatisfactory in the HER-2 mutant population, whereas the survival improvement of anti-HER-2 monoclonal antibodies and pan-HER inhibitors is limited. The development of antibody drug conjugate (ADC) ushers in a turning point for HER-2-mutated NSCLC, and new ADC drugs represented by trastuzumab deruxtecan are making a breakthrough. It opens up a new era of precision therapy for advanced HER-2-mutated NSCLC. Additionally, novel HER-2 inhibitors show very encouraging initial efficacy and safety, and clinical trials are ongoing. This review focuses on the latest progress of research on HER-2-mutated NSCLC.